Islam dan Budaya Lokal Kejawen: Moderasi dalam Kehidupan Masyarakat - Nugraha, Arya; Anil Mu'ir, M. Izza; Najmul Umam, Muhammad Mufti (CV Kalimasada Group, 2025)
This study argues that the integration of Islamic teachings and local Kejawen culture is essential to understanding the religious practices of Muslims. This argument is supported by observations of the dynamics of interaction between religious teachings and local traditions, which show that moderation (wasathiyyah) is key to creating balance and tolerance. The approach used in this study is a literature study, where the analysis of relevant texts and references explores how Kejawen adherents integrate Islamic worship with local traditions, such as selamatan and ruwah. The results of the study show that moderation is not only a theoretical concept, but also a practice that is lived in everyday life. The application of the values of tolerance and education in the context of moderation allows Muslims to appreciate diversity while maintaining their identity.